Chapter 9 Sammenhengen mellom mindfulness og eksekutiv funksjon hos profesjonelle fotballspillere - Meland, Anders (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"Mindfulness has become a popular tool for athletes, but the knowledge about the exact associations between trait mindfulness and key performance variables are lacking. This is especially problematic for athletes competing at a higher level where minor costs of a trait or an intervention could easily outweigh the benefits. In this study we investigated the association between self-reported level of mindfulness and performance on two PC based tests of inhibitory control on forty-two professional soccer players. The results showed that the observation facet of mindfulness was associated with better performance on one of the tests, while the non-judgement facet was associated with lower performance on both tests due to more impulsive responding. These findings suggest that trait mindfulness and inhibitory control is related, but that the relationship may not only be beneficial."